Comparison of prognostic models in advanced hepatocellular carcinoma patients undergoing Sorafenib: A multicenter study. Issue 8 (August 2021) - Marasco, Giovanni; Colecchia, Antonio; Bacchi Reggiani, Maria Letizia; Celsa, Ciro; Farinati, Fabio; Giannini, Edoardo Giovanni; Benevento, Francesca; Rapaccini, Gian Ludovico; Caturelli, Eugenio; Di Marco, Mariella; Biasini, Elisabetta; Marra, Fabio; et al.
Abstract: Background: Sorafenib is the gold standard therapy for the advanced hepatocellular carcinoma (HCC). No scoring/staging is universally accepted to predict the survival of these patients. Aims: To evaluate the accuracy of the available prognostic models for HCC to predict the survival of advanced HCC patients treated with Sorafenib included in the Italian Liver Cancer (ITA.LI.CA.) multicenter cohort. Methods: The performance of several prognostic scores was assessed through a Cox regression-model evaluating the C-index and the Akaike Information Criterion (AIC). Results: Data of 1129 patients were analyzed. The mean age of patients was 61.6 years, and 80.8% were male. During a median follow-up period of 13 months, 789 patients died. The median period of Sorafenib administration was 4 months. All the prognostic scores were able to predict the overall survival ( p <0.001) at univariate analysis, except the Albumin-Bilirubin score. The Italian Liver Cancer score (CLIP) yielded the highest accuracy (C-index 0.604, AIC 9898), followed by the ITA.LI.CA. prognostic score (C-index 0.599, AIC 9915). Conclusions: The CLIP score had the highest accuracy in predicting the overall survival of HCC patients treated with Sorafenib, although its performance remained poor. Further studies are needed to refine the current ability to predict the outcome of HCC patients undergoing Sorafenib.